Folic Acid Inhibited Vasculogenic Mimicry in Esophageal Cancer Cell Line Eca-109, the One Target Was EphA2. (3rd July 2022) - Xu, YuLing; Fu, LingMeng; Pan, Da; Wei, Jie; Xia, Hui; Wang, ShaoKang; Sun, GuiJu
Abstract: The degree of vasculogenic mimicry(VM) is correlated with the prognosis of esophageal cancer, and folic acid supplementation could decrease esophagus cancer deaths among populations. This study aimed to explore the effect of folic acid on VM formation of esophageal cancer cell, and the target. Human esophageal squamous cancer cell lines(Eca-109) were cultured with different concentrations of folic acid (0, 1, 10, 100, 200, 400, 600, 800 μg/ml). A cell counting kit-8 (CCK-8) assay was used to measure the cell proliferation. Then, the amount of VM under the effect of different concentrations of folic acid was observed. Target genes were screened out from several possible targets genes including MMP2, MMP9, EphA2, VE-cad or Ln-5γ2 by employing reverse transcription-quantitative polymerase chain reaction(RT-qPCR). Finally, western blot analysis was used to verify the target proteins. In conclusion, this study found that folic acid inhibited the formation of VM in Eca-109 cells, and the one target protein was EphA2.